The right to legal representation in customary courts in Botswana - Gabanagae, Mokwadi Chris (School For Advanced Legal Studies, 2026)
Botswana attained its independence on 30th September 1966. Before that it had been a British Colony since 1885. Since it attained its independence it has rapidly grown both economically and in population. Its legal system has also seen some developments. It has not been static. The country has a written Constitution which provides for three arms of government. They are the Executive, the Legislature and the Judiciary. The judiciary which is charged with administering the law consists of the court of appeal, the high court and the magistrate Courts. There is also the industrial court which deals with the labour disputes. The above mentioned courts are manned by legally trained personnel. Alongside these courts exists customary courts which have existed from ancient times and have existed until the arrival of the White man in Botswana when their operation was limited to only Africans.1 Customary courts are spread all over the country including urban areas.